Clinical presentations, diagnosis, management, and outcomes of renal mucormycosis: An overview of case reports - Didehdar, Mojtaba; Chegini, Zahra; Khoshbayan, Amin; Moradabadi, Alireza; Shariati, Aref (Frontiers in Medicine, 2022)
Background: Renal mucormycosis (RM) is a rare presentation of invasive mucormycosis with a high mortality rate. There is no single systematic review of the literature that indicates the different clinical aspects of RM. Methods: A systematic search of PubMed/Medline was performed to collect individual case reports of RM in patients of all ages published between 2010 and April 2022. Results: Seventy-one individual cases were detected through PubMed bibliographic database searches, with a final assessment performed on 60 patients with RM. India and Asia had the largest number of reported cases, with 30 (50%) and 42 (70%) reports, respectively. Also, 74% and 26% of the patients with a mean age of 33 years were male and female, respectively. RM showed 44% mortality rate in the analyzed cases. Immunosuppressive agent therapy followed by tissue transplantation (kidney and liver) and diabetes were the most remarkable risk factors in patients. Nevertheless, 22% of the patients were immunocompetent with no apparent underlying condition. COVID-19 positivity was detected in eight adult patients with an 87% mortality rate. The most common signs of infection were fever, flank pain, and oliguria; additionally, isolated RM was reported in 57% of the cases. In 55% of the patients, histopathologic examination alone was sufficient to diagnose RM, whereas molecular methods and culture were used in only 18% and 35% of patients, respectively. Surgery alone, surgery plus anti-infection therapy, and anti-infection therapy alone were used in 12%, 60%, and 13% of patients, respectively. Furthermore, 15% of the patients died before any treatment. Conclusion: The early diagnosis of RM is necessary. In this regard, the use of molecular-based diagnostic assays can help identify the fungus at the genus and species levels and use an appropriate treatment in the shortest possible amount of time. Because of the increase in antibiotic resistance in recent years, determining microbial susceptibility tests can lead to the better infection management. Additionally, withdrawal of immunosuppressant, appropriate surgical intervention, and antifungal therapy are the main factors associated with a successful outcome in RM.